Profitability and Capital Structure as Determinants of Firm Value: An Empirical Study in The Pharmaceutical Industry - Hafitriyanti, Reza Ace; Syahrudin, Muhammad; Pawitri, Wiwit (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2025)
This study investigates the influence of profitability and capital structure on firm value in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. Firm value, proxied by Price to Book Value (PBV), reflects investor perception of a company’s performance and sustainability. Profitability, measured by Return on Assets (ROA), represents managerial efficiency in utilizing assets, while capital structure, measured by Debt to Equity Ratio (DER), reflects the level of financial leverage. Using a quantitative approach with panel data regression, secondary financial data from nine purposively selected pharmaceutical firms were analyzed. Model selection procedures, including the Chow, Hausman, and Lagrange Multiplier tests, confirmed that the Random Effect Model was the most appropriate estimator. The regression results demonstrate that profitability has a positive and significant effect on firm value, indicating that firms with higher earnings performance are more highly valued by investors. Conversely, capital structure shows an insignificant effect on firm value, suggesting that leverage was not a primary consideration in investor assessments of pharmaceutical firms during the study period. Nevertheless, the simultaneous test revealed that profitability and capital structure jointly affect firm value, although profitability plays the dominant role. These findings underscore that the valuation of pharmaceutical firms in Indonesia is more strongly driven by internal financial performance than by financing structure. The study contributes updated empirical evidence by focusing on a strategically important sector in the post-pandemic context and provides practical implications for managers, investors, and regulators in enhancing profitability and ensuring sustainable growth.